Foreign presence and market concentration in Malaysian manufacturing industries. - Radziah Adam; Noor Aini Khalifah (Penerbit Universiti Kebangsaan Malaysia, 2012)
This paper examines the relationship between foreign presence and market concentration and thus competition in the Malaysian manufacturing sector by looking at the determinants of foreign presence and market concentration respectively. Using a panel of aggregate 5 digit Malaysian manufacturing industries for 2001-04 different extents and proxies of foreign presence are utilized to test the hypothesis that higher foreign presence leads to more concentrated market. The single equation results show that foreign presence,in terms of fixed assets share, has no significant impact on increasing the level of market concentration, while higher foriegn presence in an industry, in regards to both value added and employment shares, significantly contributes towards more concentrated markets.On the other hand, a highly concentrated market is also one of the significant determinants for all proxies of foreign presence, In both instances, the extent of foreign shareholdings does not matter as much the types of proxy used to measure foreign presence.However, asystem of four equations,including market concentration (under the Structure-Conduct-Performance framework) and foreign presence, estimated using Two-Stage Least Squares (2SLS) with fexid effects shows no significant evidence to support the existence of simultaneity between market concentration and foreign presence.